2016
DOI: 10.1016/j.ebiom.2015.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant-enhanced CD4 T Cell Responses are Critical to Durable Vaccine Immunity

Abstract: Protein-based vaccines offer a safer alternative to live-attenuated or inactivated vaccines but have limited immunogenicity. The identification of adjuvants that augment immunogenicity, specifically in a manner that is durable and antigen-specific, is therefore critical for advanced development. In this study, we use the filovirus virus-like particle (VLP) as a model protein-based vaccine in order to evaluate the impact of four candidate vaccine adjuvants on enhancing long term protection from Ebola virus chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 88 publications
3
54
0
1
Order By: Relevance
“…As the magnitude of the T cell response is dependent on its ability to expand in response to antigen, this assay reflects an important feature of vaccine-induced CMI (28-30). The (38); P ϭ 0.0177 b a A responder was defined as a subject with an antigen-stimulated response that was Ն2ϫ higher than that seen with the respective negative (no stimulation) control and was Ն0.02% after subtraction of the respective negative (no stimulation) control data. Where indicated, P values represent results from Fisher's exact tests comparing the number of responders to the number seen under the same stimulation conditions between day 0 and day 56; NS, not significant.…”
Section: Discussionmentioning
confidence: 99%
“…As the magnitude of the T cell response is dependent on its ability to expand in response to antigen, this assay reflects an important feature of vaccine-induced CMI (28-30). The (38); P ϭ 0.0177 b a A responder was defined as a subject with an antigen-stimulated response that was Ն2ϫ higher than that seen with the respective negative (no stimulation) control and was Ն0.02% after subtraction of the respective negative (no stimulation) control data. Where indicated, P values represent results from Fisher's exact tests comparing the number of responders to the number seen under the same stimulation conditions between day 0 and day 56; NS, not significant.…”
Section: Discussionmentioning
confidence: 99%
“…The first study, by Martins et al, was related to an Ebola-VLP vaccine with which mice had great short-term protection against Ebola challenge but lost protection over time (88). Testing a series of different adjuvants to increase long-term durable immunity showed that only poly(IC) was effective at inducing long-term immunity.…”
Section: Novel Translational and Clinical Research Strategies To Provmentioning
confidence: 99%
“…27 Protein-based vaccines are relatively less immunogenic because the potency of T-cell activation is low. 36 Thus, the ssRNA adjuvants must compensate for these deficiencies. The gE protein produced from the CHO-K1 cell expression system-induced VZV gE-specific antibody.…”
Section: Discussionmentioning
confidence: 99%